Industry 4.0 technologies in circular innovation: A review of sustainable value chain studies - Turan Azizov (Scientific Papers of the University of Pardubice, Series D: Faculty of Economics and Administration, 2024)
This paper explores the intersection of Industry 4.0 (I4.0) and the Circular Economy (CE). The paper's focus is to demonstrate how different factors, such as advanced technologies, can enable the transition of large corporations toward sustainable and circular value chains. The umbrella review has been conducted to identify key organizational enablers and technological innovations driving circularity in such organizations from an academic viewpoint. The paper presents a circular innovation framework in which technological and managerial aspects have been integrated to understand their holistic effect on different value chain steps, from product design to reverse flows. While technological aspects include multiple I4.0 technologies, such as additive manufacturing (AM), blockchain, and big data, and their use cases in the circular value chain, managerial aspects emphasize the role of stakeholders, leadership awareness, and cross-functional collaboration. The study mentions the need for a holistic approach involving all ecosystem actors to achieve a regenerative and sustainable future. This framework not only provides contributions to the academic world but also offers practical implications for large organizations seeking to enhance their circularity. The research concludes with recommendations for future studies to focus on in-depth analysis.
Keywords: Q01; Q56; L60; O32; M15; D22; 330; Circular economy; Industry 4.0; Value chain; Circular innovation framework; Umbrella review